Peripheral administration of lipidized NPAF and NPFF analogs does not influence central food intake regulation but induces anxiety-like behavior - Strnadová, Veronika; Morgan, Alena; Škrlová, Magdalena; Haasová, Eliška; Bardová, Kristina; Myšková, Aneta; Sýkora, David; Kuneš, Jaroslav; Železná, Blanka; Maletínská, Lenka (Neuropeptides, 2024)
RF-amide peptides influence multiple physiological processes, including the regulation of appetite, stress responses, behavior, and reproductive and endocrine functions. In this study, we examined the roles of neuropeptide FF receptors (NPFFR1 and NPFFR2) by generating several lipidized analogs of neuropeptide AF (NPAF) and 1DMe, a stable analog of neuropeptide FF (NPFF). These analogs were administered peripherally for the first time to investigate their effects on food intake and other potential physiological outcomes. Lipidized NPAF and 1DMe analogs exhibited enhanced stability and increased pharmacokinetics. These analogs demonstrated preserved high affinity for NPFFR2 in the nanomolar range, while the binding affinity for NPFFR1 was tens of nanomoles. They activated the ERK and Akt signaling pathways in cells overexpressing the NPFFR1 and NPFFR2 receptors. Acute food intake in fasted mice decreased after the peripheral administration of oct-NPAF or oct-1DMe. However, this effect was not as pronounced as that observed after the injection of palm11-PrRP31, a potent anorexigenic compound used as a comparator that binds to GPR10 and the NPFFR2 receptor with high affinity. Neither oct-1DMe nor oct-NPAF decreased food intake or body weight in mice with diet-induced obesity during long-term treatment. In mice treated with oct-1DMe, we observed decreased activity in the central zone during the open field test and decreased activity in the open arms of the elevated plus maze. Furthermore, we observed a decrease in plasma noradrenaline levels and an increase in plasma corticosterone levels, as well as an increase in Crh expression in the hypothalamus. Moreover, neuronal activity in the hypothalamus was increased after treatment with oct-1DMe. In this study, we report that oct-1DMe did not have any long-term effects on the central regulation of food intake; however, it caused anxiety-like behavior.
Keywords: receptory neuropeptidů; NPAF; regulace chuti k jídlu; Lipidization; 1DMe; Analogs; Behavior; Oligopeptides; HFD; úzkost; Animals; Appetite Regulation; zvířata; Food intake; myši; Mice; oligopeptidy; Anxiety; Receptors, Neuropeptide